2022
DOI: 10.3389/fmars.2022.909231
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem Services of Ecosystem Approach to Mariculture: Providing an Unprecedented Opportunity for the Reform of China’s Sustainable Aquaculture

Abstract: China is the biggest provider of mariculture products, and the industry is still growing rapidly. Increasing scientific evidence indicates that mariculture may provide valuable ecosystem goods and services in China. Here, we performed a systematic literature review of studies with the aim of understanding the ecosystem services of mariculture and a comprehensive review of ecosystem approaches that may improve mariculture ecosystem services and goods in China. We highlight four ecosystem services functions in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 81 publications
(68 reference statements)
0
3
0
Order By: Relevance
“…China is the largest mariculture producer worldwide, of which the mariculture production ranked first in 2020 (Xu et al., 2022), contributing more than 65% to the global mariculture production (Zhou et al., 2022). The main characteristics of mariculture in China are wide variety, rich diversity, low trophic levels, high ecological efficiency and large biological output (Tang et al., 2016).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…China is the largest mariculture producer worldwide, of which the mariculture production ranked first in 2020 (Xu et al., 2022), contributing more than 65% to the global mariculture production (Zhou et al., 2022). The main characteristics of mariculture in China are wide variety, rich diversity, low trophic levels, high ecological efficiency and large biological output (Tang et al., 2016).…”
Section: Methodsmentioning
confidence: 99%
“…At present, China is at the forefront of IMTA development, and this mode has been practiced in some regions: fish-shellfish-seaweed and fish-seaweed IMTA are popular in Zhejiang, Fujian, Guangdong; shrimp-shellfish IMTA is popular in Shandong and Jiangsu; shellfish-seaweed IMTA has been deployed in almost all coastal regions of China; mangrove-restoration-based IMTA has been developed in Guangxi (Zhou et al, 2022). On this basis, some studies have estimated the ecological benefits of the IMTA system based on ecosystem services evaluation: Tang et al (2013) investigated the service value of food provision and climate regulation under different mariculture modes in Sanggou Bay, and their results showed that the service value provided by IMTA was much higher than that of single mariculture mode.…”
Section: Transformation Potential Of Mariculture From Ecological Burd...mentioning
confidence: 99%
“…Currently, research on ecological efficiency primarily centers around the following aspects: (1) Research objects of ecological efficiency. Scholars have combined the concept of eco-efficiency with economic production practices, involving industry [5][6][7][8], energy [9,10], marine [11][12][13][14], agriculture [15,16], tourism [17,18], urban development [19][20][21][22] and many other fields. The economic and environmental performance was evaluated via an empirical method, and ecological efficiency was used as an optimization strategy in the actual production process.…”
Section: Introductionmentioning
confidence: 99%
“…As the largest mariculture country, China accounted for 65.9% of global mariculture production in 2018 . Consequently, large amounts of mariculture wastewater (MWW) containing organic and nitrogen substrates are produced and pose a serious threat to marine ecosystems .…”
Section: Introductionmentioning
confidence: 99%